Since angles ∠KLM and ∠MLP are supplementary, we know that the sum of their measures is 180°. Given:
- m∠KLM = (x + 30)°
- m∠MLP = (2x + 60)°
We can write the equation for supplementary angles as:
\[ m∠KLM + m∠MLP = 180° \]
Substituting the expressions for the angles, we get:
\[ (x + 30) + (2x + 60) = 180 \]
Now, we can combine like terms:
\[ x + 30 + 2x + 60 = 180 \]
This simplifies to:
\[ 3x + 90 = 180 \]
To write the equation in the requested form:
\[ 3x + 90 = 180 \]
Thus, the final equation is:
\[ 3x + 90 = 180 \]